Il paziente accompagnatore: Dante incontra Virgilio - Paolo Zuppi; Julia Klein; Carlo Resti; Elisabetta Rossi; Marta Casini (AM. Rivista della Società Italiana di Antropologia Medica, 2022)
The Accompanying Patient: Dante Meets VirgilIllness changes personal and social identity. Biomedicine offers only a technical response without meeting the needs of the sick man. Dialogue with a person who has already gone through the same difficulties is profoundly beneficial. Effective care must be intertwined with different skills, roles and contributions in a network of threads / friendships, dynamic, trans-actional, inter-active, multidimensional intersubjective, ontonomic, which reflects human complexity; a network that can support an in-firm in its arduous path of realization. Il paziente accompagnatore: Dante incontra VirgilioLa malattia modifica l’identità personale e sociale. La biomedicina offre solo una risposta tecnica senza esaurire i bisogni dell’uomo malato. Il dialogo con una persona che abbia già attraversato le stesse difficoltà è profondamente benefico. La cura efficace deve intrecciare competenze, ruoli e contributi diversi in una rete di fili/amicizie, dinamica, trans-azionale, inter-attiva, intersoggettiva multidimensionale, ontonomica, riflesso della complessità umana, rete che può sostenere l’in-fermo nel suo faticoso percorso di realizzazione.